Competitive advantage analysis: a novel method for industrial clusters identification - Stejskal, Jan; Hajek, Petr (Journal of Business Economics and Management, 2012)
Many regions and their representatives decide on the amount of support they will provide to industrial clusters, their births, and their existing phase based on the public budget. Nowadays the efficiency of public spending must be provided. There are many examples showing situations where industrial clusters were cancelled when public support was limited or no longer available. Through the use of a special diagnostic method, one can find out if the industrial cluster is able to rise and also be viable without massive public budget support. The suggestion of a new method for industrial cluster identification is the aim of this paper. The Porter's diamond model of the cluster's competitiveness environment is the substance of the novel method.